ORGANIZATIONAL CULTURE, WORK MOTIVATION, AND WORK EFFECTIVENESS (CASE STUDY ON HOTELS IN TOMOHON AND TONDANO) - Jenny Nancy Kaligis; Steven Set Xaverius Tumbelaka; Devis Goni (AIBPM Publisher, 2023)
The purpose of this study is to determine the influence of organizational culture and work motivation both partially and simultaneously on the effectiveness of employee work in five hotels in Tomohon And Tondano Cities. For the method used in this study, namely the quantitative method using a sample of 73 employees, and to analyze the data in this study, multiple regression analysis was used. The results found in this study, namely organizational culture and work motivation, both partially and collectively, affect the effectiveness of employee work. Presumably, with the conduct of this study, parties from the five hotels in Tomohon and Tondano Cities can fix the shortcomings that affect the effectiveness of employee work as explained in this study, as well as for subsequent researchers who will conduct research with the same variables and objects as those in this study, not plagiarizing from this study, but rather it only makes this research a reference or reference.